Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1039/c6ob01092j
|View full text |Cite|
|
Sign up to set email alerts
|

Synthesis and immunological evaluation of MUC1 glycopeptide conjugates bearing N-acetyl modified STn derivatives as anticancer vaccines

Abstract: Glycoprotein MUC1 is an attractive target for anti-tumor vaccine development. However, the weak immunogenicity of MUC1 remains a significant problem. To solve this problem, several STn derivatives with N-acetyl modifications were synthesized and incorporated into a 20-amino acid MUC1 tandem repeat sequence. The modified STn-MUC1 glycopeptides were further connected to a carrier protein keyhole limpet hemocyanin (KLH). The immunological effects of these synthetic vaccine conjugates were evaluated using the BALB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 33 publications
0
9
0
1
Order By: Relevance
“…mimetic was also able to activate iNKT cells, when conjugated to a phospholipid carrier, which enabled the mimetic to be presented in the context of the conserved nonpolymorphic MHC class I-like molecules (CD1d) [279]. Modification at the N-acetamido position of the galactose residue of MUC antigens and in the sialic acid containing antigens (e.g., GM3, sTn, sTF) has likewise been widely investigated [280][281][282][283].…”
Section: Glycomimetics In the Discovery Of Anticancer Glycoconjugate Vaccinesmentioning
confidence: 99%
“…mimetic was also able to activate iNKT cells, when conjugated to a phospholipid carrier, which enabled the mimetic to be presented in the context of the conserved nonpolymorphic MHC class I-like molecules (CD1d) [279]. Modification at the N-acetamido position of the galactose residue of MUC antigens and in the sialic acid containing antigens (e.g., GM3, sTn, sTF) has likewise been widely investigated [280][281][282][283].…”
Section: Glycomimetics In the Discovery Of Anticancer Glycoconjugate Vaccinesmentioning
confidence: 99%
“…Tumor associated carbohydrate antigen (TACA) played a crucial role as a biomarker in the tumorigenesis and development, and it has attracted considerable attention. [ 64‐66 ] The globo‐H is a hexasaccharide containing fucose, glucose, galactosamine and galactose units. Huang and coworkers synthesized globo‐H by utilizing preactivation‐based one‐pot four component [1+2+1+2] glycosylation (Scheme 20).…”
Section: Application Of Preactivation Strategy In the Assembly Of Olimentioning
confidence: 99%
“…Several STn derivatives with N ‐acetyl modifications were synthesized, they were then incorporated into a MUC1 peptide and were further connected to KLH. The evaluation results of the synthetic vaccine conjugates demonstrated that the carbohydrate antigen modification strategy has the potential to improve immunogenicity of natural MUC1 glycopeptides …”
Section: Advances In Tacas Based Cancer Vaccinesmentioning
confidence: 99%
“…The evaluation results of the synthetic vaccine conjugates demonstrated that the carbohydrate antigen modification strategy has the potential to improve immunogenicity of natural MUC1 glycopeptides. 205…”
Section: Cross-reactivity-based Cancer Vaccinesmentioning
confidence: 99%